Colonial Turkestan: contemporary foreign historiography on resettlement politics (Journal of history, 2020)
Success of the Russian presence in Turkestan was determined by character of colonialism and imperialismwhich was transferred to the soil of Turkestan in 1870-1900s. This is a key question to understanda nature and goals of the national liberation movements that emerged within this period on the territoryof empire. Political trajectories of the Russian empire development depended, to a certain degree, onthe results of Turkestan colonization. Would the empire be able to complete successfully “civilizing colonialism”mission and within what range it was possible to realize? The answers to these questions weredue to the administration and Russian capital achievements in Turkestan – the only empire’s colony.In this article the author ties to analyze an array of problems raised in the works of British historian A.Morrison. He is actively involved into studies of Russian colonial society’s problems in pre-revolutionaryTurkestan. Morrison dwells on the nature of metropole – colony relations to focus on the results of fundamentalchanges in Turkestan governor general and its differences form the other Moslem populatedimperial areas.